Penguatan Literasi Qur’ani dan Pemahaman Furudul Ainiyah bagi Santri: Program Pendampingan di Daerah Al-Amiri Pondok Pesantren Nurul Jadid - Bashori Alwi; Radit, Raditiya Anggara Putra; Ifril, Ahmad Ifril Aufia Shonhaji; Luthfi, Muhammad Luthfi Azizy; Iqrom, Mohammad Iqrom (Yayasan Literasi Altruis Khatulistiwa, 2025)
The Quran Reading and Writing (BTQ) and Furudul Ainiyah (Islamic Religious Affairs) Mentoring in the Al-Amiri Area of Nurul Jadid Paiton Probolinggo Islamic Boarding School is a form of community service that focuses on strengthening the basic religious abilities of students, especially those who are still in the depths of high school and below. The background to the implementation of this program departs from the reality of the gap in the ability of students to read the Quran and the understanding of fardhu 'ain sciences such as fiqh, aqidah, and morals. This mentoring is very important because reading the Quran and understanding Furudul Ainiyah is an individual obligation (fardhu 'ain) which is the main foundation in the life of a Muslim. In addition, it also provides an understanding of tafaqquh fid-din and is expected to be able to provide a solution for Islamic Boarding Schools regarding the importance of maintaining and developing students' understanding in the field of religion. This mentoring uses the Community-Based Participatory Research (CBPR) method, which is a partnership approach involving management members, religious teachers, and the researchers themselves. This is intended to ensure that activities continue even after the mentoring has concluded. From the evaluation results, it is proven that this mentoring has a positive and significant impact, especially in the development of the Qur'an and the deepening of furudul ainiyah, a culture of mutual assistance has emerged, strengthening Islamic brotherhood, and strengthening the tradition of studying yellow books and the Qur'an and being able to practice furudul ainiyah material.